Landasan Pendidikan Akhlak menurut HAMKA - Fuadi, Syifa Tsamrotul; Bisri, Hasan; Sumadi, Sumadi (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Moral education is education which is about the basics of morals (morals) and the virtue of character, the traits a child must have from childhood until he becomes a convert. Morals are closely related to human thought patterns, attitudes and behavior. Good morals or noble morals are attitudes and behaviors that must be possessed by every Muslim, either directly related to Allah Almighty, or to His creatures. Regarding the moral education, the researcher studied the thoughts of Haji Abdul Malik Karim Amrullah (HAMKA), a prominent scholar from Minangkabau. This study is to determine the moral education according to HAMKA, both for students and for the community. Moreover, some of HAMKA's thoughts on Islamic Education, many say that the form of all his thoughts on the issue of Education is to emphasize more on mental education or morals. The objectives of this research are: 1) To know the basis of moral thought according to HAMKA, 2) To know the purpose of moral education according to HAMKA, and 3) To find out the moral education according to HAMKA and its relevance to Islamic religious education. This study uses library research (library research) with descriptive analysis method, namely by collecting data, compiling and classifying, compiling and interpreting it. This descriptive study was carried out by collecting data, classifying the data, then formulating the rules for compliance contained in the data. The results of the research conducted by the intruder is that according to HAMKA, the moral basis is an inner temper that can change so that if it arises based on reason and religion, a good character will emerge and vice versa if it arises not based on reason and religion, a bad character will appear or is often called with a despicable character. The sources of moral education according to HAMKA are the Koran, Assunah, tawhid, and reason.